If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + x = 6x + -16 Reorder the terms: 2 + x = -16 + 6x Solving 2 + x = -16 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 2 + x + -6x = -16 + 6x + -6x Combine like terms: x + -6x = -5x 2 + -5x = -16 + 6x + -6x Combine like terms: 6x + -6x = 0 2 + -5x = -16 + 0 2 + -5x = -16 Add '-2' to each side of the equation. 2 + -2 + -5x = -16 + -2 Combine like terms: 2 + -2 = 0 0 + -5x = -16 + -2 -5x = -16 + -2 Combine like terms: -16 + -2 = -18 -5x = -18 Divide each side by '-5'. x = 3.6 Simplifying x = 3.6
| 10.7x+91.71=-9.3x+90.97 | | -31=-6x-9 | | 28+32c=92 | | 0.3+0.6m=0.6m-0.6 | | -3x+7=-28 | | 21.31=1.00x+4.31 | | X+3=-21+5x | | 15-2w=w+12w | | 2x-20=3x+10 | | x+25=34.50 | | 10x+50=8x+60 | | 3x+25=50 | | 0.666666666666667x-0.166666666666667=0.5+0.833333333333333 | | y=2.65(200)+4.50 | | 19=7r-2(3+4r) | | x^2+75=2x^2 | | 2x+1=6x-35 | | 4n-11=-3 | | 8n=-3m+l | | 200=2.65x+4.50 | | v+1=v+6 | | 2x+6-5x=6x-12 | | x-6=-11 | | 2x+7(x-3)=15 | | 4n-11n=-3 | | .2x^2-1.1x+.5=0 | | 0.875p-0.25=0.5p | | x+7=4-2x | | 0.875p-0.25=0.25p | | 14v+2=19v-3 | | y=-3*1-3 | | 0.5(6c-4)=4+c |